Performance of a compression ignition engine fuelled by diesel and imitated syngas - Mahgoub, B. K. M. (2012)
Biomass can be converted into a useful source of energy through gasification. The gasification product, which is a mixture of gases, is known as synthesis gas or syngas. The composition of syngas fluctuates due to many factors such as operational errors of the gasifier as well as the type of feedstock used or the feeding rate fluctuation. Therefore it is difficult to assess the effect of syngas composition and diesel replacement ratio to the performance when combusted in a compression ignition engine. In order to overcome this problem, controllable composition and conditions of imitated syngas is used in this study by selecting three compositions of syngas close to the real conditions. The objective of this study is to ascertain the possibility of using syngas as alternative to diesel fuel for an internal combustion engine while providing acceptable engine performance. The test results on syngas performance are compared with the results for diesel at engine speed of 2000 rpm. The results of the performance test of both fuels are examined in terms of the engine’s power output, exhaust temperature, brake specific fuel consumption, brake thermal efficiency, and volumetric efficiency. It is generally shown that the use of syngas leads to lower brake power and brake thermal efficiency. In addition, different syngas compositions are shown to respond differently to the engine performance.